The Importance of Non-Verbal Communication in Mediation - e Silva, Raphael Parreira; Jothimuni, Manoj Suranga (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Non-verbal communication is a critical component of dispute resolution, particularly in mediation. A thorough understanding of non-verbal cues enhances the ability of mediators and involved parties to interpret emotions, recognise cultural differences, and appreciate underlying values. This article examines the significance of non-verbal communication in mediation, emphasising its role in facilitating effective resolutions and mutually beneficial agreements. The research argues that a deeper awareness of non-verbal interactions enables mediators to interpret participants’ intentions better and strengthens their ability to foster collaboration and guide disputes toward satisfactory outcomes. Furthermore, it highlights how mastering non-verbal communication enhances the mediator’s professional and interpersonal effectiveness, ultimately improving the human aspect of the mediation process.